Non-targeted 1H-NMR-metabolomics suggest the induction of master regulators of energy metabolism in the liver of vitamin E-deficient rats1. Issue 4 (8th April 2015) - Moazzami, Ali A.; Frank, Sonja; Gombert, Antonin; Sus, Nadine; Bayram, Banu; Rimbach, Gerald; Frank, Jan
<x xml:space="preserve">Abstract</x> Consumption of a vitamin E-deficient diet for 6 months may alter hepatic energy metabolism in rats.